Semantic and Scientific Interpretation of Al-Zill (Shadow) in the Qur'an: A Semantic-Based Tafsir ‘Ilmi of Surah al-Furqan (25:45–46) in Light of Geometric Optics - Mudin, Moh. Isom; Sabilillah, Muhammad; Suharto, Ahmad; Saifuddin, Ahmad Farid (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
Shadows as observable natural phenomena are described in the Qur’an, particularly in Surah al-Furqān (25:45–46), which portrays their extension, movement, and relation to the sun. This study aims to analyze the concept of al-ẓill (shadow) in these verses through a semantic-based approach to tafsīr ‘ilmī and to examine its conceptual correlation with principles of geometric optics. The research employs a qualitative textual method using a three-layered analytical framework consisting of semantic deconstruction, exegetical mapping, and conceptual correlation. The first stage analyzes key Qur’anic terms—madda, ẓill, dalīlan, and qabḍnāhu—through classical Arabic lexicons and semantic field analysis. The second stage examines interpretations from classical and modern exegetical works to trace the historical understanding of the verses. The third stage explores the conceptual alignment between the Qur’anic description of shadows and established principles of geometric optics concerning shadow formation and solar geometry. The findings indicate that the Qur’an describes shadows as dynamic and orderly phenomena governed by the position of the sun, reflecting a coherent observational pattern compatible with scientific explanations of shadow formation and variation. Rather than presenting scientific predictions, the Qur’anic narrative offers a phenomenological description of natural processes that invites reflection on cosmic order and divine wisdom. This study contributes a methodological model for interdisciplinary research that integrates semantic analysis of Qur’anic language with responsible engagement with scientific knowledge.